Let's (not) talk about synthetic biology: Framing an emerging technology in public and stakeholder dialogues. (July 2020) - Bauer, Anja; Bogner, Alexander
Synthetic biology is an emerging technoscience, which, so far, lacks a broader public debate. To foster early societal dialogue, a range of public engagement events have been initiated over the past decade. This article discusses the configurations of the emerging debate on synthetic biology in the context of the EU FP7 project SYNENERGENE. Drawing on notions of frames and framing in media studies and policy analysis, we ask which distinct frames are invoked and become dominant in current discussions about synthetic biology. Our analysis indicates significant reconfigurations in the framing of synthetic biology compared with previous biotechnology debates. Frames that traditionally served to problematize biotechnology, that is, ethics, risks, and economics, become less dominant. Instead, the potential to contribute to social progress is placed in the foreground. Moreover, discussions on ethics, risks, and governance frequently occur on an abstract level, invoking generic statements that could be made for any new technology.